How Can Engaging Communities Aid in Developing New Conservation Initiatives? - Omondiagbe, Harriet (Auckland University of Technology, 2016)
The field of environmental conservation is experiencing a greater awareness of the social complexities involved when implementing conservation goals, while the process for effectively engaging stakeholders, especially communities, remains challenging. I investigated how engaging a community could aid in developing new conservation initiatives within a pest management context, with the aim of contributing to a Predator Free New Zealand by 2050. This thesis demonstrates the potential for successful collaborations while engaging communities in developing conservation strategies. Firstly, I explored the role of Sense of Place in pest management planning. Next, I identified conservation actors, analysed their relationships and examined the potential for collaboration within their social networks. Lastly, I employed Living Lab principles of value, influence, realism, sustainability and openness to assist stakeholders in developing pest management strategies for their community. I designed the study within a pragmatism paradigm, employing a sequential mixed method approach and involving theories from different disciplines. The study proposed that conservation strategies with minimal or no impact on a community’s sense of place would likely be adopted without strong opposition and vice versa. Stakeholders’ position within their social networks could influence collective action that could favour conservation goals. By engaging communities in conservation planning; conservation goals developed are relevant; public opposition could be minimised; a momentum could be generated for conservation action and there is an increased likelihood that conservation goals would be achieved. The results of this study offer expectation for the feasibility of a predator-free New Zealand; however, the issues identified in this thesis have to be addressed before this expectation can become a reality.
Keywords: Social network; Sense of place; Living Laboratory; Predator Free 2050; Predator Free New Zealand; Waiheke Island; Pragmatism; Pest management; Island communities; Community engagement; Applied Conservation; Conservation Biology; Conservation planning